A Regional Static Model of the Dammam Aquifer as a Source of Injection Water, Southern Iraq - Abdullah, Rafea A.; Ismael, Maher; Sadoon, Ahmed; Ahmed, Masara; Alameri, Reyam; Abdulhameed, Maysaa A. (Journal of Petroleum Research and Studies, 2024)
The Middle Eocene, shallow, dolomitic, high salinity aquifer has significant importance as the main source of injection water at the present time in order to maintain reservoir pressure above the bubble point in maturing oil fields in southern Iraq until other sources of injection water become available. Therefore, in this study, the Dammam aquifer was studied in detail by integrating all available data, including 3D seismic, well information, well logs, and core data. A regional aquifer static model has been constructed to better understand subsurface geology and in order to be ready to be used in the construction of a sophisticated dynamic model to predict whether the Dammam aquifer can supply enough water for injection or not. More than 184 wells have been used in the present study. The structural framework was built according to 3D seismic cube and well tops. The average thickness is about 235 mm. In order to understand the lateral and vertical connectivity, a facies model was created in addition to the porosity and permeability models with input from the core and a Nuclear Magnetic Resonance (NMR) log. According to the facies change, the Dammam aquifer has been divided from bottom to top into five units (MD50, MD100, MD200, MD300, and MD400). The top of the Dammam formation varies from 700m in the southeast to 1000m in the north-west. The porosity in the Dammam formation is very high and varies from 12 to 45 PU, with an average porosity of 29 PU. In order to reduce uncertainty, the study recommends that a new rock core have to be cut, in addition to a number of NMR and Formation Micro Imager (FMI) logs needing to be run into selected wells